Comprehensive management of chest wall recurrent HER2-positive breast cancer with Anlotinib and hypofractionated radiotherapy: a case report - Xu, Jing; Liu, Qing; Yin, Yue; Dong, Guanglu (Frontiers in Oncology, 2026)
HER2-positive breast cancer (BC) patients who have developed resistance to various systemic therapies face limited treatment alternatives. Literature on Anlotinib combined with hypofractionated radiotherapy (HFRT) for recurrent/metastatic HER2-positive BC is scarce, particularly for Trastuzumab-resistant cases. This report describes an unresectable, bulky HER2-positive BC recurrence in a patient who had an inadequate response to multiple systemic treatments, including chemotherapy, Trastuzumab, immunotherapy, and conventional fractionated radiotherapy (CFRT). Upon observing further progression of the chest wall mass, we initiated a treatment regimen that combined Anlotinib with HFRT. Remarkably, after just one cycle of this combined therapy, the tumor exhibited considerable shrinkage, with the patient now remaining in remission. These findings indicate that Anlotinib, in conjunction with HFRT, may be a promising option for patients with unresectable chest wall recurrence(CWR), particularly for those who have previously undergone Trastuzumab therapy but subsequently developed resistance.